4CPS-082 Most frequent errors in the inhalation technique of asthmatic children. Issue 1 (23rd March 2023) - Rhaymi, C; Chaibi, A
Abstract : Background and Importance: Asthma is a real public health problem. Inhalation therapy is the mainstay of the management of this chronic disease. one of the most important reasons for failed therapy is improper inhaler technique. Aim and Objectives: Demonstrate the most frequent errors in the technique of inhalation in asthmatic children treated in our establishment Material and Methods: A prospective observational study was conducted with asthmatic children admitted to our establishment over a period of 2 months. We have developed an evaluation grid for the inhalation technique. it was considered correct when all steps were performed correctly. Results: A total of 50 patients were included. The average age was 3.7 years. Inhalers observed were metered-dose inhalers. All patients declared having had a demonstration of the inhalation technique mainly by their doctor. Among 50 participants, 30 (60%) performed the inhalation technique incorrectly. Errors were most common at the stage of slow, full, deep breathing as recommended by the guidelines (70%), followed by no spray agitation (15%). Conclusion and Relevance: Our results support poor inhaler technique in children that may have adverse consequences on therapeutic efficacy. The educational role of the clinical pharmacist is very important to improve the proper use of the inhalation technique and the management of patients. References and/or Acknowledgements: 1. No conflict of interest. Conflict of Interest: No conflict of interest.